PENGARUH MODAL, LAMA USAHA, JAM KERJA DAN LOKASI USAHA TERHADAP PENDAPATAN PEDAGANG DI PASAR LANDUNGSARI - Budi Prihatminingtyas (Unitri Press, 2019)
The purpose of this study is to explain the effect of: (1) capital; (2) business duration; (3) working hours; and (4) business location on the income of traditional traders in the Landungsari market, Malang city. The population are 388 traders, which the data collected with likert scale to measure attitudes, opinions and perceptions of someone related to social phenomena. Data analysis technics using quantitative data, and multiple linear regression analysis. The results showed that: (1) capital has a significant and positive effect on the income of traders in the Landungsari market, which daily capital in the form of money is used as initial capital to help traders sell; (2) business duration has a negative effect on the income of traders in the Landungsari market, which the length of business that is less than 1 year needs to improve the approach skills to consumers; (3) working hours have a negative effect on the income of market traders in Landungsari, but working hours in the morning are quite promising because many consumers visit the market to shop for various needs; (4) business location has a positive effect on the income of traders in the Landungsari market in Malang.